GREEN URINE AND ALTERED MENTAL STATUS: A CASE OF INTOXICATION - Gangwani, Manesh Kumar; Aziz, Muhammad; Asif, Rana; Ali, Syed Ahsan (Journal of Ayub Medical College Abbottabad, 2019)
Green coloured urine is atypical as it usually signifies the presence of an exogenous substance. Several substances in literature have been associated with green urine including propofol, biliverdin, metoclopramide, methylene blue, indigo blue, amitriptyline, methocarbamol, indomethacin, promethazine, cimetidine and food colourings. We present here a case of middle-aged man who presented to our ER with altered mental status and green coloured urine with positive urine toxicology reports for benzodiazepine. Keywords: Benzodiazepine; Green Urine; Overdose; Toxicology; Emergency Medicine